Pagamentos por serviços ambientais e a formulação de políticas públicas - Paula, Camila de (2023)
Payment for environmental services (PSA) is a voluntary transaction whereby a payer of environmental services transfers to a provider of such service’s financial resources or other form of remuneration, subject to the right conditions, and legal regulation. The concept was defined in January 2021, with the publication of Law No. 14.119, establishing the National Policy and the Federal Environmental Services Payment Program and, although it does not represent innovation on the subject, these are the programs already developed at state level, municipal and regional, the new law was developed to meet the demand for national standardizing guidelines. Nevertheless, the adoption of measures for the establishment of a National Environmental Service Payment Register is still lacking. The lack of integration between government data related to the Environmental Services Payment results in significant number of divergences of information that may cause inconsistencies that could undermine the management of public policies in this environmental sphere. As Public Policies are one-off actions taken by the government to safeguard the social and collective rights provided by law, this work aims to propose a structuring, integration of payment information for environmental services through a database that allows the state power to improve its activity in this sector, with increased efficiency and reduction of inconsistencies. For the development of the work, a bibliographic and documentary review was carried out with an overall analysis of the data for the development of the theoretical reference and research of applied and developing studies. Finally, there was detailed and individualized consultation in all the municipalities of the field of study, to verify the existence of projects, the stage and the externalities generated. The study was conducted in the Municipality of Curitiba and in its metropolitan region and as a result, found a diversified region in terms of environmental services, but with few programs in development, with decentralized information and difficult to access. It is therefore concluded that the database proposed in this work will contribute as a support tool to the development of public policies.